STATELINE. [Indoor Air Pollution and Ventilation 1988 State and Local Legislation] (Tufts Archival Research Center, 2007)
Tobacco Institute special Stateline report summarizing 1998 state and local indoor air pollution and ventilation legislation. Lists states that have introduced such legislation and discusses those which request investigative study. Summarizes state ventilation regulations. Adresses four local ordinances, all of which have to do with ventilation standards and do not specifically deal with indoor air pollution.